2015
DOI: 10.1021/acs.inorgchem.5b00476
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Catalysis of Diazene E/Z Isomerization

Abstract: Nitric oxide is an efficient catalyst for the cis-trans (E/Z) isomerization of diazenes. We compare the effect of room temperature solutions bearing low concentrations of nitric oxide, nitrogen dioxide, or oxygen on the rate of cis-trans isomerization, CTI, of the alkene bond in stilbene and on the azo double bond in azobenzene, as well as in four azo derivatives as measured by UV-vis spectroscopy. These rate enhancements can be as large as 3 orders of magnitude for azobenzene in solution. A mechanism is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Surprisingly, enhancements can be detected for all nitrogen positions including the amino group, presumably due to the existence of the enamine–imine tautomer, which is structurally similar to Schiff bases (or indirect polarization transfer). Diphenyldiazene (entry 11) exhibits E / Z isomerism induced optically, , or chemically . Interestingly the Z form is hyperpolarized exclusively despite the fact that the E form is thermodynamically stable.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, enhancements can be detected for all nitrogen positions including the amino group, presumably due to the existence of the enamine–imine tautomer, which is structurally similar to Schiff bases (or indirect polarization transfer). Diphenyldiazene (entry 11) exhibits E / Z isomerism induced optically, , or chemically . Interestingly the Z form is hyperpolarized exclusively despite the fact that the E form is thermodynamically stable.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Diphenyldiazene (entry 11) exhibits E/Z isomerism induced optically, 49,50 or chemically. 51 Interestingly the Z form is hyperpolarized exclusively despite the fact that the E form is thermodynamically stable. Enhancements of the Z-form, in presently unknown low concentration, significantly exceed 40fold (see SI).…”
Section: ■ Methodsmentioning
confidence: 99%
“…Azo compounds are usually synthesized through a diazotization coupling reaction, with asymmetric structures (as shown in Scheme a). However, the novel colorants developed in this study are biscatecholic azobenzene compounds with a symmetric structure, and their precursors, the azo chromophores, are suitable to be synthesized via an oxidization–coupling reaction, where aromatic amines can self-couple to form azo bonds (as shown in Scheme b). Based on the symmetric structure, two dopamine molecules could be simply incorporated into the azo chromophore through a one-step reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…47 In prior publications, we have found that B3LYP/6-311++G** is an excellent combination of method and model for the ground-state geometries and vibrational modes or electronrich nitrogen species with multiple lone pairs such as these. 48,49 Here, the inclusion of diffuse functions is an important factor. 50,51 This is the case for these urea starting materials and hydrazine products, which have theoretically calculated ground-state structures and vibrational modes (supplementary information S28-S31) that match well the expected intensities and positions of the experimental data.…”
Section: Resultsmentioning
confidence: 99%